The Effect of Current Ratio, Total Assets Turn Over, Firm Size on Debt Payout Ratio with Return on Investment as Intervening Variables - Deni Sunaryo; Etty Puji Lestari (CV ODIS, 2022)
The purpose of this study is to explain the effect of the current ratio, total assets turn over and firm size on the dividend payout ratio in cash with return on investment as an intervening variable. In this study, the object of this research is the retail sub-sector companies in Southeast Asia for the period 2012-2019. The sample method used in this study is a purposive sampling technique where the data obtained are 17 companies from 136 populations. The analytical technique used is the r2 test, multiple linear regression analysis, t & f test, path analysis and Sobel test. The results of the study partially conclude that the current ratio has a significant effect on the dividend payout ratio, while tattoos and firm size have no significant effect on dividend payout. ratio. Simultaneous test results also show that the current ratio, tattoo and firm size simultaneously have no significant effect on dividend payout ratio and current ratio, tattoo and firm size also have no effect on return on investment. The relationship between variables for return on investment has a significant effect on the dividend payout ratio and return on investment is unable to mediate the effect of the current ratio, tattoo and size on the dividend payout ratio. The results of this study can be used as a consideration in determining dividend payments and can be expected to assist financial managers in making a decision to determine the amount of dividends that can be paid, especially in the form of cash dividends